Antioxidant capacity and hydrogen peroxide formation by black and orange carrots: Black and orange carrots - Bartosz, Grzegorz; Baran, Sabina; Grzesik-Pietrasiewicz, Michalina; Sadowska-Bartosz, Izabela (Agricultural and Food Science, 2022)
Anthocyanins are powerful antioxidants with numerous beneficial health effects. However, their autoxidation may produce hydrogen peroxide. Black carrots owe their colour to the high anthocyanin content. The aim of this study was to compare the antioxidant capacity of and hydrogen generation by black and orange carrots. Black carrots were found to have a significantly higher anthocyanin content and antioxidant capacity estimated by the FRAP assay, DPPH scavenging and ABTS• scavenging. Carrot, like other vegetables, generates hydrogen peroxide upon cooking. Black carrots generated much more hydrogen peroxide than orange carrots (55.0 ± 2.6 µM vs 6.0 ± 2.1 µM in phosphate buffer, 8.7 ± 1.2 vs 0.3 ± 0.1 µM in water, in 1:5 (w/v) homogenates. These small amounts of hydrogen peroxide are not likely to exert deleterious health effects but may have antimicrobial activity.